2017
DOI: 10.5812/jjnpp.64313
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genetically Engineered Dioxygenase Producing Pseudomonas putida on Decomposition of Oil from Spiked Soil

Abstract: Background: It is well known that bioremediation or using microorganism enzymes plays an important role in decomposition and changing of oil pollutants and PAH compounds into nonhazardous or less-hazardous substances. The genetically manipulated bacteria like Pseudomonas sp. can enhancement the natural biodegradation activity of polycyclic aromatic hydrocarbons (PAHs) in polluted cities. Pseudomonas putida (P. putida) is a saprotrophic soil bacterium that is found throughout various environments such as soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…40 Mardani et al used genetically manipulated Pseudomonas putida for oil biodegradation in spiked soil and could significantly increase biodegradation of PAHs in the recombinant group. 41 Tarhriz et al isolated and introduced Tabrizicola aquatica as the novel genus of aquatic bacteria from qurugol Lake in the mountains region of Azerbaijan which can adsorb heavy metals. 42 Elyasifar et al isolated halophilic bacterial belonged to Bacillus subtilis and Virgibacillus olivae, from Dagh Biarjmand and Haj Aligholi salt deserts in Iran with potential to produce antibacterial and antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…40 Mardani et al used genetically manipulated Pseudomonas putida for oil biodegradation in spiked soil and could significantly increase biodegradation of PAHs in the recombinant group. 41 Tarhriz et al isolated and introduced Tabrizicola aquatica as the novel genus of aquatic bacteria from qurugol Lake in the mountains region of Azerbaijan which can adsorb heavy metals. 42 Elyasifar et al isolated halophilic bacterial belonged to Bacillus subtilis and Virgibacillus olivae, from Dagh Biarjmand and Haj Aligholi salt deserts in Iran with potential to produce antibacterial and antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the lack of full genes and enzymes/enzyme systems of PAH conversion in bacteria, the open-loop genes (such as the phn gene clusters and nah -like gene clusters) and hydrocarbon degradation pathways could be introduced into core strain by molecular engineering strategies. Some studies have indicated that the biodegradation of PHE and PYR in soil could be enhanced by over-expression of the nahH gene (encoding catechol 2,3-dioxygenase) in Stenotrophomonas maltophilia (Mardani et al, 2017 ). During the exogenous gene C23O that encoded catechol 2,3-dioxygenase was introduced into the alkane-degrading bacterium Acinetobacter sp .…”
Section: Artificial Mms Construction Strategymentioning
confidence: 99%
“…Another investigation has reported the biodegradation of oil and PAH compounds from the soil using recombinant bacterial strain Pseudomonas putida. This bacterial strain was cloned with catechol 2,3-dioxygenase (C23O) encoded gene (nahH) suing pUC18 vector [73]. Liu et al [74] genetically modified the methanotroph Methylomonas sp.…”
Section: Microbial Bioremediationmentioning
confidence: 99%